Potential role of key rumen microbes in regulating host health and growth performance in Hu sheep - Ximei Xie; Huan Yang; Xingang Zhao; Li Teng; Yuze Yang; Hailing Luo (Animal Microbiome)
Abstract Background Average daily gain (ADG) is an important component affecting the profitability of sheep. However, research on the relationship between rumen microbes and sheep growth phenotype is still very lacking. Therefore, in this study, 16 Hu sheep were selected from a cohort of 318 sheep assigned to the same feeding and management conditions, and divided into high growth rate (HADG, n = 8) group and low growth rate (LADG, n = 8) group according to the extreme ADG value. Then, the differences in rumen microbes, rumen fermentation and animal immune parameters were further compared between groups to explore the potential role of rumen key microbes in regulating the health and growth performance of Hu sheep hosts. Results The results showed that specific pathogenic bacteria associated with ADG, including Anaerotruncus, Sediminibacterium and Glaesserella, exhibited significant correlations with interleukin-6 (IL-6) and immunoglobulin G (IgG). These interactions disrupt immune homeostasis in the host, leading to a metabolic prioritization of energy resources toward immune responses, thereby impairing growth and development. Succinivibrio_dextrinosolvens was enriched in HADG sheep and exhibited a significant positive correlation with propionate levels. This promoted propionate production in the rumen, enhancing the metabolic activity of carbohydrate, amino acid and energy metabolism, ultimately contributing to higher ADG in sheep. Importantly, random forest analysis results showed that Succinivibrio_dextrinosolvens could classify sheep into HADG and LADG with a prediction accuracy of 81.2%. Additionally, we identified 34 bacteria belonged to connectors in the HADG co-occurrence network, including Alloprevotella, Phascolarctobacterium, Anaerovibrio, Butyricicoccus, Ruminococcaceae_noname, and Roseburia, etc., which play an important role in the degradation of carbohydrates and convert them into short-chain fatty acids (SCFAs), maintaining rumen health, and modulating inflammation. Conclusions In summary, key microbes in the rumen affect the overall healthy homeostasis and rumen fermentation of the host, leading to changes in energy utilization, which in turn affects the average daily gain of Hu sheep. Succinivibrio_dextrinosolvens is a promising biomarker for selecting high growth rate sheep in the future. This study provides a new method to manipulate rumen bacteria to improve growth performance in sheep. Graphic abstract